Public equipment at Residencial Cachoeirinha in Botucatu SP - Vieira, Carlos Eduardo; Salcedo, Rosio Fernandez Baca; Pasquotto, Geise Brizotti (National Journal of City Management, 2024)
Regarding the existing housing deficit in Brazil, the public authorities have opted to build housing complexes on the outskirts of cities, where the supply of public equipment is already precarious for residents, to the detriment of installing housing in central areas with already consolidated infrastructure. This study will not seek to discover the cause or reasons for this choice, but rather, given this fact, how this situation could be better planned by the public authorities, causing less impact on the new inhabitants. Public facilities, such as schools, health centers, access to urban transport, are essential for improving the population’s quality of life, regardless where they live. They guarantee a feeling of belonging to the city life, thus largely avoiding isolation from other residents. This study analyzes the construction of the Cachoeirinha Residential Complex in the Botucatu city in São Paulo State, relating it to the existing public equipment on site, before and after its installation, using, in addition to a bibliographical analysis on the subject, the coverage radius methodology of basic education, health and leisure services, seeking to identify whether or not they meet the criteria for locating these equipment. As a result, deficiencies were revealed in relation to some equipment, suggesting the need for more effective planning and a more appropriate resources allocation to remedy such weaknesses.